Determinant of Sea Salt Aerosol Emission in the Southern Hemisphere in Summer Time. Issue 11 (16th November 2022) - Shi, Jun; Yan, Jinpei; Wang, Shanshan; Zhao, Shuhui; Zhang, Miming; Xu, Suqing; Lin, Qi; Yang, Hang
Abstract: High‐time resolution (1h) aerosol composition measurements were performed in the Southern Hemisphere during February 2018–April 2018. Na + was the most abundant water‐soluble ion (WSI) species, accounting for 67% of the total WSIs. The highest Na + levels were observed in low‐middle latitudes (20–40°S) with an average concentration of 2.69 ± 2.16 μg m −3 . This was 2–3 times greater than in other regions. Low temperature ( T ) and strong short‐term variations of wind speed (WS) were associated with relatively low Na + concentrations in high‐middle latitudes (40–60°S), where there was a strong mean WS (9.1 m s −1 ). When WS < 7 m s −1, Na + concentrations were low in all T ranges. Temperature and Na + concentrations were moderately positively correlated when 10 ≤ WS < 13 m s −1 and WS ≥ 13 m s −1 ( R 2  = 0.48 and 0.34, respectively). Na + concentrations were very low when relative humidity (RH) < 60% and significantly increased when RH was between 70% and 90%. However, Na + concentrations under high RH (90%–100%) were not higher than those with RH between 70% and 90%, implying that a number of fine particles will increase their mass and convert to coarse particles and lead to a greater gravity sedimentation in high RH. Close to the Antarctic, Na + concentrations decreased significantly under high WS levels, suggesting that sea ice cover reduces the production of sea salt aerosols (SSAs). What's more, air mass trajectory and the source of air mass also had an effect on the concentrations of SSAs. The results presented here extend the knowledge of the impact of sea salt on atmospheric aerosols above the Southern Hemisphere Ocean. Key Points: Marine aerosols were determined with high‐time‐resolution in the Southern Hemisphere Sea salt aerosols (SSAs) emissions would be increased with the air temperature The concentrations of SSAs do not always increase with the increases of wind speed